2017
DOI: 10.1039/c7cc05646j
|View full text |Cite
|
Sign up to set email alerts
|

Specific and spatial labeling of choline-containing teichoic acids in Streptococcus pneumoniae by click chemistry

Abstract: Propargyl-choline was efficiently incorporated into teichoic acid (TA) polymers on the surface of Streptococcus pneumoniae. The introduction of a fluorophore by click chemistry enabled sufficient labeling of the pneumococcus, as well as its specific detection when mixed with other bacterial species. The labeling is localized at the septal site, suggesting a similar location of the TA and peptidoglycan (PG) synthetic machineries. This method is a unique opportunity to improve our understanding of the spatial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…A recent study (40) suggested the presence of a type I LTA besides the type IV LTA in S. mitis based on the identification of a potential biosynthetical intermediate, glycerophospho-diglycosyl-diacylglycerol (GPDGDAG). However, the authors of that study also reported the identification of GPDGDAG in S. pneumoniae and S. oralis , which do not contain type I LTA (18,22,41), what is further corroborated by the absence of LtaS in these species as elucidated here. Moreover, the mentioned work of Wei et al (40) showed by using an LtaS-knockout of S. mitis strain ATCC 49456 (SM61; NCTC12261) that GPDGDAG synthesis does not require LtaS.…”
Section: Discussionsupporting
confidence: 81%
“…A recent study (40) suggested the presence of a type I LTA besides the type IV LTA in S. mitis based on the identification of a potential biosynthetical intermediate, glycerophospho-diglycosyl-diacylglycerol (GPDGDAG). However, the authors of that study also reported the identification of GPDGDAG in S. pneumoniae and S. oralis , which do not contain type I LTA (18,22,41), what is further corroborated by the absence of LtaS in these species as elucidated here. Moreover, the mentioned work of Wei et al (40) showed by using an LtaS-knockout of S. mitis strain ATCC 49456 (SM61; NCTC12261) that GPDGDAG synthesis does not require LtaS.…”
Section: Discussionsupporting
confidence: 81%
“…The choline-growth dependency of S. pneumoniae has been exploited to incorporate choline molecules bearing small functional groups ready for click chemistry when incorporated into the TAs polymers. Using Cu(I)-catalyzed azide-alkyne cycloaddition, fluorescent reporters were grafted to TAs decorated with the chemically modified choline molecules in a specific and selective manner ( Di Guilmi et al, 2017 ). This method has been adapted to live cells using copper-free bioorthogonal click reaction and fluorescent reporter such as DIBO-Alexa Fluor 594 (Bonnet et al , submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Choline is not rare in bacteria but S. pneumoniae is the only known species whose growth entirely depends on exogenous choline which is exclusively integrated into the TAs. We recently took advantage of this choline growth dependency to label pneumococcal TAs with chemically-modified fluorescent choline molecules using a bioorthogonal reaction related to the click chemistry approach ( Di Guilmi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, no broadly applicable technique is available for labeling of teichoic acids in Gram-positive bacteria. However, the unique feature of S. pneumoniae to incorporate choline into teichoic acid has enabled the use of propargyl-choline as a bio-orthogonal probe for metabolic labeling of teichoic acids that can be detected via CuAAC [139].…”
Section: Targeting Other Components Of the Cell Envelopementioning
confidence: 99%